Endophthalmitis at a tertiary referral center: Characteristics and treatment outcomes over three decades - Zhang, Wen-Fei; Zhao, Xin-Yu; Meng, Li-Hui; Chen, Huan; Chen, You-Xin (Frontiers in Cell and Developmental Biology, 2022)
Purpose: To explore the incidence, pathogens, treatment, and prognosis of endophthalmitis. Methods: Patients who were diagnosed with endophthalmitis from January 1990 to October 2020 at Peking Union Medical College Hospital were retrospectively reviewed and examined. Subgroup analysis was conducted regarding different initial treatment methods for eyes without concurrent retinal detachment (RD) at presentation. Results: A total of 249 eyes of 233 patients were included in this retrospective study. The most common clinical scenario was exogenous endophthalmitis (60.6%). The most frequent bacteria and fungi were coagulase-negative staphylococci (10.0%) and candida (6.8%), respectively. Retinal with/without choroid detachment was the most common complication after treatment. Patients with endogenous endophthalmitis were more likely to have binocular involvement; there were also more patients with diabetes mellitus or immunosuppressive diseases, and the prognosis of visual acuity (VA) was poorer. There were more eyes with concurrent RD at presentation that underwent serious complications after treatment (p < 0.05), and the visual outcome was worse than that without concurrent RD (p < 0.05). Subgroup analysis was conducted according to different initial treatments in eyes without concurrent RD. Group 1 received pars plana vitrectomy (PPV) with intravitreal injection of antibiotics (IVI) as initial treatment, Group 2 was initially treated with IVI only, and Group 3 was initially treated with nonsurgical treatment. More eyes that initially received IVI alone and nonsurgical treatment required additional treatments, especially additional PPV. VA in both Groups 1 and 2 significantly improved by the final VA. However, there was no significant difference in final VA between the two groups. There was an insignificant trend that serious posttreatment complications were more common in Group 1. In Group 1, 17 eyes received silicone oil or gas tamponade at the same time, whereas 62 did not. Eyes that were initially treated with PPV + IVI while without tamponade needed more additional treatments and additional IVI. Conclusion: Endophthalmitis is a devastating intraocular disease and requires early intervention. Endogenous endophthalmitis has a poorer visual prognosis than exogenous entity. PPV + IVI as an initial treatment may reduce additional therapy.